Economic evaluation of biodiversity: importance of protection and representation, the impact of flaws of legislation and evaluation studies of the Baltic Sea - Ružs, Sandis (Riga Graduate School of Law, 2018)
The importance of biodiversity is undeniable. It is a supporting ecosystem service that is made up of a variety of species and underpins the environment and forms the basis for the functioning of other ecosystem services. The aim of the thesis is to present the economic significance of biodiversity in general and in the Baltic Sea region as well as to present the flaws of the Marine Strategy Framework Directive and economic evaluation of ecosystem services studies in the Baltic Sea that could impact the implementation of maintaining marine biodiversity.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Environmental law; Marine biodiversity; Economy of the Baltic Sea region